'Dokumenty!' : . "Dokumenty!" : diskriminacija po rasovomu priznaku v Rossijskoj Federacii (Amnesty International Publications, 2003)
Call nr. 2008/2539 = Russian edition. Call nr. 2008/4764 = Spanish edition. Call nr. 2008/4765 = Arabic edition. Call nr. 2008/4767 = French edition.